RANCANG BANGUN SISTEM PERINGATAN DINI BAHAYA AKTIVITAS GUNUNG BERAPI BERBASIS MIKROKONTROLER ARDUINO - Vincensio Simon, Michael Angelo; Setiawan, Widyadi; Sastra, Nyoman Putra (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p6, 2020)
This research aims to design and build an early warning system device of volcano activity hazards based on Arduino microcontroller that can monitor changes in temperature, soil moisture and tremor through sensors placed in the environment around the crater. This early warning system of volcano activity hazards is relatively simple but can be very useful to help government institutions and also the public which will reduce the risk of data collection directly and also speed up the public to get information so that they can avoid the radius of danger. The early warning system of volcano activity hazards is also flexible with wifi coverage areas that range more than 100 meters. Based on research and test that has been done shows that the system created has a good effectiveness and flexibility which is able to send monitoring results to the ThingSpeak and then display it on a smartphone application in realtime.